Influence of the deGennes extrapolation parameter on the resistive state of a superconducting strip - Barba-Ortega, J.; Sardella, Edson [UNESP]; Zadorosny, R. [UNESP] (Elsevier, 2018)
We studied the resistive state of a mesoscopic superconducting strip (bridge) at zero external applied magnetic field under a transport electric current, Ja, subjected to different types of boundary conditions. The current is applied through a metallic contact (electrode) and the boundary conditions are simulated via the deGennes extrapolation length b. It will be shown that the characteristic current–voltage curve follows a scaling law for different values of b. We also show that the value of Ja at which the first vortex–antivortex (V–Av) pair penetrates the sample, as well as their average velocities and dynamics, strongly depend on the b values. Our investigation was carried out by solving the two-dimensional generalized time dependent Ginzburg–Landau (GTDGL) equation.
Keywords: deGennes parameter; Ginzburg–Landau; Mesoscopics